1986
DOI: 10.1136/ard.45.10.847
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase isoenzymes of the synovial fluid in rheumatoid arthritis and in reactive arthritides.

Abstract: and the 3Department of Rheumatology, Sahlgren's Hospital, S-413 45 Gothenburg, Sweden SUMMARY The activity of superoxide dismutase isoenzymes was determined in knee joint synovial fluid from 21 patients with rheumatoid arthritis, nine patients with reactive arthritides, and from 17 patients before arthroscopy or arthrotomy for suspected meniscal or ligament injury (controls). Extracellular superoxide dismutase was the major isoenzyme and accounted for about 80% of the total superoxide dismutase activity in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 24 publications
3
50
0
Order By: Relevance
“…In the present study, EC-SOD and catalase were chosen as therapeutic genes. All three types of SOD have been detected in rheumatoid joints, 14,15 but EC-SOD is the only secreted isoenzyme existing in extracellular fluids including synovial fluid and tissue. Furthermore, the relatively long half-life of EC-SOD (20 h) enables it to be efficient in scavenging superoxide radicals.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, EC-SOD and catalase were chosen as therapeutic genes. All three types of SOD have been detected in rheumatoid joints, 14,15 but EC-SOD is the only secreted isoenzyme existing in extracellular fluids including synovial fluid and tissue. Furthermore, the relatively long half-life of EC-SOD (20 h) enables it to be efficient in scavenging superoxide radicals.…”
Section: Introductionmentioning
confidence: 99%
“…This was achieved by sampling all sites for the same length of time (5 minutes). [13,14] In this study, the results revealed that the activity level of superoxide dismutase was significantly higher in the gingival tissues in the chronic periodontitis group (9.50 ± 2.11 U/ml) as compared to the control group (5.89 ± 0.74 U/ml). This finding seems to confirm several findings in the medical literature about oxidant-antioxidant balance.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, a reduction in SOD3 has been noted in numerous diseases. Patients with rheumatoid arthritis exhibit a 50% reduction in SOD activity compared with normal controls, suggesting that reduced SOD activity contributes to endothelial dysfunction in patients with this disease (32). Similarly, SOD3 expression is substantially reduced in patients with coronary artery disease (24).…”
Section: Discussionmentioning
confidence: 99%